TREND WISATAWAN SENIOR DALAM MEMILIH AKTIVITAS WISATA DAN HARAPANNYA TERHADAP SEBUAH DESTINASI PARIWISATA - Utama, I Gusti Bagus Rai (Jurnal Ekonomi dan Pariwisata, 2017)
ABSTRACT Senior tourists are potential, this is due to the improvement quality of life, and the quality of medical technology, increasing of income, and other 16actors that impact to human life expectancy is getting longer. The study is related to senior travelers which have not been done by previous researchers especially for Bali. Therefore, based on these considerations, research of senior tourists subject need to be conducted because the preferences of tourists are dynamic and tend to the higher demands on the quality of a tourism destination. Object of this study is senior tourists on age of 55 years or more, and hereinafter referred to senior travelers. Senior travelers studied are derived from foreign tourists. This study uses desk research with data retrieval techniques and information by online method, secondary data, and references from scientific publications. While the analytical technique used is descriptive technique analysis, analogy, and comparatively few research and other publications related to senior travelers. The results of this study are expected to be useful in theoretical and practical especially those related to market segmentation, customer satisfaction, especially senior tourists. The activities identified such as shopping, city tour, visiting historic sites, museums, heritage, get lunch or dinner in restaurants, watching television shows, radio listening, social activities, activities related to the hobby, the distribution of talent associated with the craft, and the distribution of talent that relates to the art. It mean that package to realize the motivation of senior tourist should be found on tourism destination because there is relationship of citizenship to the motivation of senior tourists traveling to a tourist destination. To realize tourist satisfaction, the destinations should always effort to realize the quality of products to fit the expectations of senior tourists by high quality product that also related to the motivations of senior tourist as conclusions. Keyword: usia lanjut, wisata, preferensi, wisatawan, perilaku, aktivitas.